Chronic Myeloid Leukemia with an e6a2 BCR-ABL1 Fusion Transcript: Cooperating Mutations at Blast Crisis and Molecular Monitoring. (16th October 2017) - Crampe, Mireille; Haslam, Karl; Groarke, Emma; Kelleher, Eileen; O'Shea, Derville; Conneally, Eibhlin; Langabeer, Stephen E.
Abstract : A minority of chronic myeloid leukemia patients (CML) express a variety of atypical BCR-ABL1 fusion variants and, of these, the e6a2 BCR-ABL1 fusion is generally associated with an aggressive disease course. Progression of CML to blast crisis is associated with acquisition of additional somatic mutations yet these events have not been elucidated in patients with the e6a2 BCR-ABL1 genotype. Moreover, molecular monitoring is only sporadically performed in CML patients with atypical BCR-ABL1 fusion transcripts due to lack of consensus approaches or standardization. A case of CML is described in which comprehensive molecular analysis, including targeted next-generation sequencing, revealed a single ASXL1 mutation cooperating with an e6a2 BCR-ABL1 fusion transcript at blast crisis. A quantitative molecular monitoring approach was devised and adopted that reflected the disease response from initial treatment through allogeneic stem cell transplantation which resulted in undetectable e6a2 BCR-ABL1 transcripts. This case emphasizes the requirement for molecular monitoring in CML patients with atypical BCR-ABL1 fusion transcripts and emphasizes that comprehensive sequencing has the potential to identify targets for novel therapies in CML patients with advanced disease.